Enhancing social inclusion through local dialogues on natural resource management (NRM) - Elias, Marlène; Priyadarshini, Pratiti; Meinzen-Dick, Ruth S.; Ghate, Rucha; Rao, Jagdeesh (2020)
The purpose of this tool is to stimulate thinking and offer guidance on a tested approach for enhancing social inclusion in and through natural resource management (NRM). It can be used to accompany processes of community engagement and community-based or -led deliberations on NRM or other topics of local importance. The approach described draws attention to the importance of representation, process as well as content in fostering inclusion in NRM or other community affairs. It represents a facilitated process of community engagement to enhance social inclusion and cohesion, and the prospects of collective action to work through situations of discrimination or conflict via inter-group contact under a set of predefined conditions. This process can allow groups to better know and understand each other, work through their differences, and create group unity. The approach is rooted in dialogue and represents a process of active engagement among participants, accompanied by both women and men facilitators, over time. It can be applied to fields other than NRM.